ANALYSIS OF BUSINESS DEVELOPMENT IN THE ROTI YULFA LABULANGO INDUSTRY TO REDUCE UNEMPLOYMENT - Harold, Rudi; Mahyun, Safitri; Butulo, Andre; Sali, Intan; Olii, Risti; Husin, Nur Alin; Nusi, Abdul Rizal (PERSPEKTIF: Journal of Social and Library Science, 2025)
The bakery industry plays a vital role in the Indonesian economy, particularly in absorbing labor and reducing unemployment. However, most research is macro-scale, thus under-representing the dynamics of micro-scale business development. This study aims to analyze the business development strategy of Roti Yulfa Labulango, its contribution to employment, and the challenges faced. The study used a qualitative approach with a case study design on Roti Yulfa Labulango, which has been operating since June 2019 on Jl. Bali, Pulubala, Kota Tengah, Gorontalo City, with one owner and six employees. Data were collected through in-depth interviews, production process observations, and operational documentation, then analyzed inductively and thematically. The results show that the bread product diversification strategy (pandan, peanut, chocolate, mocha, and banana), production scheduling, and clear task allocation increased production capacity, product quality, and workforce skills and stability. This business development was able to absorb direct and indirect labor, including local residents, thus contributing significantly to reducing local unemployment.